Potential of Essential Oil Eucalyptus botryoides Leaves as an Antibacterial in Hand Sanitizer - Andi Nur Fitriani Abubakar; Syahdam Karneng; Firnanelty Firnanelty; Rezki Nur Damayanti; St. Aisyah; Ahmad Bikharuddin (Walisongo Journal of Chemistry, 2022)
Hand sanitizer is an antiseptic product that is widely used to prevent the spread of bacteria and viruses. Hand sanitizer preparations circulating in the market still use alcohol as an antibacterial agent. One of the natural antibacterial Eucalyptus is an antibacterial agent, and essential oil extracted from Eucalyptus can be named as natural ingredient. The purpose of this study was to determine the potential of essential oil E. botryoides leaves as an antibacterial ingredient to make of hand sanitizer. Eucalyptus essential oil is extracted from its leave using steam distillation method and formulated in the making of hand sanitizer gel with various concentrations of 2%, 4%, and 6%. The formulation of hand sanitizer gel was tested for antibacterial, organoleptic, homogeneity, pH, and dispersibility. The results showed that the more concentration of essential oil from Eucalyptus botryoides leaves added to the hand sanitizer gel, the more its antibacterial activity increased. The results of organoleptic observations, homogeneity, pH, and dispersibility of hand sanitizer gel preparations have met the requirements of SNI No.06-2588-1992. Thus, essential oil from E. botryoides leaves has potential as an antibacterial in hand sanitizer gel products.